KEPRIBADIAN ATLET KARATE PPLOP JAWA TENGAH DARI SUDUT PANDANG GENDER (Indonesian Journal for Physical Education and Sport, 2021)
Purpose of this study has to determine the personality profile of male karate athletes and female karate athletes of PPLOP Central Java. The method used is a survey through a quantitative approach. The sample in this study amounted to 10 with details of 6 men and 4 women with a total sampling technique. The data collection instrument was carried out using an SPQ 20 questionnaire distributed online with 168 questions. The data analysis used in this research is descriptive exploration of SPSS The results of the study obtained that women excel in the aspects of Achievement 4.33, Adaptability 4.75, Competitiveness 4.79, Conscientiousness 4.63, Visualization 4.64, Intuition 4.00 , Goal Setting 4.56, Managing Pressure 3.96, Self Efficacy 4.25, Fear of Failure Control 3.67, Flow 4.69, Stress Management 4.63, Emotion 4.31, Self Talk 4.83, Self Awareness 4.75 and Ethics 4.90. Meanwhile, men have better Personality than women in 3 aspects, namely Relationships 3.88, Aggressiveness 3.27 and Power 3.04. It can be concluded that women have better personality than men in the aspects of Achievement, Adaptability, Competitiveness, Conscientiousness, Visualization, Intuition, Goal Setting, Managing Pressure, Self Efficacy, Fear of Failure Control, Flow, Stress Management, Emotion, Self Talk, Self Awareness and Ethics. Almost all of them have significant differences between male athletes and female athletes. And there is no significant difference in the Empathy item.